Morrás, María (2000) «PETRARCA, BRUNI, VALLA, PICO DELLA MIRANDOLA, ALBERTI, Manifiestos del humanismo» - Jorge García Lopez (Swervei de publicacions, 2001)
Morrás, María (2000)PETRARCA, BRUNI, VALLA, PICO DELLA MIRANDOLA, ALBERTI, Manifiestos del humanismo